Stigmatizing language and visuals in reporting on children in Indonesia - Yumelda Sari; Sarwititi Sarwoprasodjo; Pudji Muljono; Amiruddin Saleh (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2025)
This study analyzed the compliance of Indonesian online media with the Child-Friendly Reporting Guidelines (PPRA) and UNICEF Guidelines, focusing on stigmatizing language and visual representation of children. A total of 282 news articles published in January, June, and December 2024 by Sindonews.com (national) and Poskota.co.id (local) were examined through quantitative content analysis. The coding instrument consisted of 117 indicators, with this article emphasizing 41 indicators related to language and visuals. The findings revealed moderate compliance. While anonymity protocols were generally applied, stigmatizing terms and degrading narratives remained frequent, especially when reporting children as perpetrators. Visuals often blurred children’s faces but still exposed contextual identifiers such as homes and schools. These practices undermine child protection. The study concluded that ethical reporting requires empathetic language, safe visuals, and stronger monitoring by the Press Council.